Associative dynamics in the informal economy: urban transportation in Angola - Lopes, Carlos M. (2010)
This article explores some of organizational and representative processes currently seen in urban transportation in two Angolan cities, Luanda and Huambo. It describes two distinct organizational models: governmental intervention seeking to regulate the moto-taxis in Huambo, which has led to the creation of the Association of Mototaxi Operators of Angola (AMOTRANG), and the spontaneous appearance and growth, in Luanda’s minibus segment, of informal associations, called “staffs”, whose goal is the professional and social protection of its members. The article also presents information regarding the appearance and growth of semi-official and informal urban transportation in each city.